2020
DOI: 10.1101/2020.09.08.287052
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring genetic resistance to Infectious Salmon Anaemia Virus in Atlantic salmon by genome-wide association and RNA sequencing

Abstract: Infectious Salmonid Anaemia Virus (ISAV) causes a notifiable disease that poses a large threat for Atlantic salmon breeders and producers worldwide. There is no fully effective treatment or vaccine, and therefore selective breeding to increase resistance to ISAV in commercial strains of Atlantic salmon is a promising avenue for disease prevention. Genomic selection and potentially genome editing can be applied to enhance host resistance, and these approaches benefit from improved knowledge of the genetic and f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 81 publications
2
14
1
Order By: Relevance
“…A previous study showed similar results during early infection, with a more important up-regulation of interferon genes in the head kidney than in other tissues [34]. However, the interferon response was previously shown to be up-regulated also in other tissues, for instance in liver [35], and in these animals we previously found it down-regulated in the heart [13].…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…A previous study showed similar results during early infection, with a more important up-regulation of interferon genes in the head kidney than in other tissues [34]. However, the interferon response was previously shown to be up-regulated also in other tissues, for instance in liver [35], and in these animals we previously found it down-regulated in the heart [13].…”
Section: Discussionsupporting
confidence: 84%
“…In head kidney, two copies of the E3 ubiquitin-protein ligase HERC3 were upregulated in response to the virus at 14 dpi. In our previous study in the same population, a gene of the same family (HERC4) co-located with a putative QTL for resistance to ISAV [13]. Additionally, another gene of this family, HERC5, was previously described as an antiviral protein in Influenza virus infection, catalysing ISGylation of NS1 and avoiding its interaction with the antiviral protein kinase R (PKR), which reduces viral propagation [47].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations